2019
DOI: 10.1186/s12911-019-0952-3
|View full text |Cite
|
Sign up to set email alerts
|

Staff expectations for the implementation of an electronic health record system: a qualitative study using normalisation process theory

Abstract: BackgroundGlobal evidence suggests a range of benefits for introducing electronic health record (EHR) systems to improve patient care. However, implementing EHR within healthcare organisations is complex and, in the United Kingdom (UK), uptake has been slow. More research is needed to explore factors influencing successful implementation. This study explored staff expectations for change and outcome following procurement of a commercial EHR system by a large academic acute NHS hospital in the UK.MethodsQualita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 74 publications
(73 reference statements)
2
18
0
Order By: Relevance
“…In our case, the clinical champion served as an intermediary between the study team and the Epic software analysts, facilitated prioritization, and identified the EHR menu button location to ensure visibility. Clinicians' input in the integration process is reported to potentially cause the sustained use of the tools in practice [41,42] and is key to an integration effort, regardless of the format or mode of delivery [14,[43][44][45].…”
Section: Results In Contextmentioning
confidence: 99%
“…In our case, the clinical champion served as an intermediary between the study team and the Epic software analysts, facilitated prioritization, and identified the EHR menu button location to ensure visibility. Clinicians' input in the integration process is reported to potentially cause the sustained use of the tools in practice [41,42] and is key to an integration effort, regardless of the format or mode of delivery [14,[43][44][45].…”
Section: Results In Contextmentioning
confidence: 99%
“…Thus, healthcare workers generally endorse the idea of an EHR, which raises the question whether EHR implementation should actually be associated with an increase in autonomous motivation. However, as EHR systems were originally developed to support billing, administration, and regulation of healthcare [ 64 ], healthcare workers often experience practical struggles with the system and frustrations about usability issues and a lack of compatibility between the EHRs and their clinical work [ 19 , 30 , 45 ]. Because the quality of their clinical work is so important for healthcare workers, the struggles and frustrations that follow from working with these systems in clinical practice might negatively affect their intrinsic motivation, and might counteract the positive consequences of EHR implementation on autonomous motivation through an increased sense of identified regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the following paragraphs, we will argue that two specific work characteristics are particularly relevant in case of EHR implementation, and are especially likely to affect satisfaction of the basic psychological needs for autonomy and relatedness: job autonomy and interdependence . Note that, in this study, we do not consider the need for competence [ 8 ], as we anticipate that feelings of competence are more likely to be affected by the quality of training, IT skills and ‘teething troubles’ of the system [ 7 , 19 , 30 ], which are not the main focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, healthcare workers generally endorse the idea of an EHR, which raises the question whether EHR implementation should be associated with an increase in autonomous motivation. However, as EHR systems were originally developed to support billing, administration and regulation of healthcare [59], healthcare workers often experience struggles with the system and frustrations about usability issues and a lack of compatibility between the EHRs and their clinical work [19,29,44]. The struggles and frustrations that follow from working with these systems in clinical practice might negatively affect healthcare workers' intrinsic motivation, and might counteract the positive consequences of EHR implementation on autonomous motivation through an increased sense of identi ed regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we will argue that two work characteristics are particularly relevant in case of EHR implementation, namely; job autonomy and interdependence, which are likely to affect satisfaction of the basic psychological needs for autonomy and relatedness. We do not consider the need for competence [8], as we anticipate that feelings of competence are particularly likely to be affected by the quality of training, IT skills and teething troubles of the system [7,19,29], which are not the main focus of this study. Job autonomy.…”
Section: Work Characteristicsmentioning
confidence: 99%